Nutritional status of indigenous children younger than five years of age in Mexico: results of a national probabilistic survey Estado nutricio de los niños indígenas menores de cinco años de edad en México: resultados de una encuesta nacional probabilística - Juan A Rivera; Eric A Monterrubio; Teresa González-Cossío; Raquel García-Feregrino; Armando García-Guerra; Jaime Sepúlveda-Amor (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To compare the prevalence of undernutrition and anemia in indigenous and non-indigenous children <5 years of age at the national level, by region and by urban and rural areas, and to evaluate the degree to which the socioeconomic condition of the family predicts the differences. MATERIAL AND METHODS: A national probabilistic survey was conducted in Mexico in 1999. Indigenous families were identified as those in which at least one woman 12-49 years of age in the household spoke a native language. The prevalence of undernutrition (stunting, wasting and underweight) and anemia was compared between indigenous and non-indigenous children. Probability ratios (PR) were used to compare prevalences in indigenous and non-indigenous children adjusting for socioeconomic status (SES) of the family and for other covariates. RESULTS: The prevalences of stunting and underweight were greater in indigenous than in non-indigenous children. At the national level and in urban areas the prevalences were three times greater and in rural areas ~2 times greater (p<0.05). No differences were found in the prevalence of wasting (p>0.05). The prevalence of anemia in indigenous children was one third greater than in non-indigenous children at the national level (p<0.05) and was between 30 and 60% greater in urban areas and in the regions studied (p<0.05) but was not statistically significant (p>0.05) in rural areas. These differences were reduced to about half when adjusting for SES but remained significantly higher in indigenous children (p<0.05). CONCLUSIONS: Indigenous children have higher probabilities of stunting and underweight than non-indigenous children. The differences are larger in urban areas and in higher socioeconomic geographic regions and are explained mostly by socioeconomic factors. The overall difference in the probability of anemia is small, is higher only in urban relative to rural areas, and is explained to a lesser degree by socioeconomic factors. Policy and programs should be designed and implemented to reduce the dramatic differences in nutritional status between indigenous and non-indigenous children in Mexico. OBJETIVO: Comparar las prevalencias de desnutrición y anemia en niños indígenas y no indígenas menores de cinco años de edad en el ámbito nacional, por región, por zonas urbanas y rurales, y evaluar en qué medida la condición socioeconómica de la familia predice las diferencias. MATERIAL Y MÉTODOS: Se realizó una encuesta nacional probabilística en 1999 en México. Las familias indígenas fueron identificadas como aquellas en las cuales al menos una mujer entre 12 y 49 años de edad en el hogar hablara una lengua indígena. Las prevalencias de desnutrición (baja talla, emaciación y bajo peso) y anemia fueron comparadas entre niños indígenas y no indígenas. Se utilizaron razones de probabilidad para comparar prevalencias ajustando por las condiciones socioeconómicas de la familia y por otras variables. RESULTADOS: Las prevalencias de baja talla y de bajo peso fueron mayores en indígenas que en no indígenas. En el ámbito nacional y en zonas urbanas las prevalencias fueron casi tres veces mayores, mientras que en zonas rurales fueron ~2 veces mayores (p<0.05). No se encontraron diferencias en las prevalencias de emaciación (p>0.05). La prevalencia de anemia en indígenas fue un tercio mayor que en no indígenas en el ámbito nacional (p <0.05) y entre 30 y 60% mayor en áreas urbanas y en las regiones estudiadas (p<0.05), pero no fue estadísticamente significativa en áreas rurales (p>0.05). Estas diferencias se redujeron aproximadamente a la mitad al ajustar por las condiciones socioeconómicas, pero continuaron siendo significativamente superiores en niños indígenas (p<0.05). CONCLUSIONES: Los niños indígenas tienen mayor probabilidad de presentar baja talla y bajo peso que los no indígenas. Las diferencias son mayores en áreas urbanas y en las regiones geográficas con mejores condiciones de vida, y se explican principalmente por factores socioeconómicos. La probabilidad de anemia entre poblaciones fue sólo modestamente mayor en zonas urbanas que en zonas rurales, y las diferencias son explicadas en menor grado por factores socioeconómicos. Se recomienda el diseño y aplicación de políticas y programas para eliminar las diferencias abismales en estado nutricio entre niños indígenas y no indígenas en México.